Detrital shocked zircon provides first radiometric age constraint (<1472 Ma) for the Santa Fe impact structure, New Mexico, USA - Montalvo, P.; Cavosie, Aaron; Kirkland, C.; Evans, N.; McDonald, B.; Talavera, C.; Erickson, T.; Lugo-Centeno, C. (Geological Society of America, 2019)
The Santa Fe structure in northern New Mexico is one of the few confirmed impact craters in the western USA. The history of the impact structure is obscure as it is tectonized and eroded to the extent that an intact crater is not preserved, and what remains is located in a complex geological setting. Shatter cones and shocked quartz were previously cited to confirm an impact origin; however, estimates for both impact age (350–1200 Ma) and crater diameter (6–13 km) remain poorly constrained. To further evaluate the extent of shock deformation, we investigated ~6600 detrital zircon grains for shock features, using material collected from 15 drainages and other sites within an ~5 km radius of known shatter cone outcrops. Six detrital shocked zircon grains were found at three locations, including two near shatter cones and one near brecciated granitoid. Follow-up studies of bedrock at two sites proximal to detrital shocked zircon occurrences led to the discovery of shocked zircon in situ in a shatter conebearing sample of biotite schist; shocked grains were not found in brecciated granitoid at the second site. Electron backscatter diffraction confirms the presence of {112} shock-twin lamellae in five shocked zircon grains, and secondary ion mass spectrometry U-Pb data for three detrital shocked grains yielded 207Pb/206Pb crystallization ages from 1715 ± 22 to 1472 ± 35 Ma. Laser ablation– inductively coupled plasma–mass spectrometry U-Pb ages for detrital zircon grains at five of the investigated sites provide the first broad constraints on the local distribution of Paleo- to Mesoproterozoic bedrock in the area. The presence of shock-twinned zircon indicates that some exposed rocks at the Santa Fe structure may record impact pressures up to ~20 GPa based on empirical studies, which is higher than previous reports of ~10 GPa based on planar deformation features in shocked quartz. The 1472 ± 35 Ma date from a shock-twinned zircon yields the first direct radiometric maximum age constraint on the Santa Fe impact event, and expands the possible time period for impact to the Mesoproterozoic. Identification of shocked zircon in modern sediment led to the first discovery of shocked zircon in bedrock at this site, which is notable, as shocked zircon is otherwise not abundant in the studied rock samples. This study thus illustrates that detrital zircon surveys are an efficient way to search for diagnostic evidence of shock deformation at putative impact structures where shocked minerals may be present, but are not abundant in exposed bedrock